SYSTEMATIC REVIEW OF BIOMARKERS FOR DISEASE PROGRESSION IN ALZHEIMER'S DISEASE. Issue 11 (9th October 2013) - McGhee, David; Counsell, Carl
Abstract : Objectives: Undertake a systematic review to assess what potential surrogate markers for disease progression in Alzheimer's disease exist, whether any meet the criteria for use in clinical trials, and if not which looks most promising. Methods: Literature searches were conducted in MEDLINE (1950 to 2011) and Embase (1980 to 2011). Five separate search strategies were run in each database. The first four were based on free–text words identified through background reading of relevant review articles. These searches included potential 1 blood, 2 urine or cerebrospinal fluid (CSF), 3 imaging and 4 neurophysiological biomarkers. A fifth search using generic terms for biomarkers based on index headings was also run in both databases. The electronic searches were limited to human studies. Reference lists of included articles and relevant review articles were checked to identify any studies which the electronic search strategy may have missed. We included studies of participants with a diagnosis of probable Alzheimer's disease made by applying formal criteria. Studies which included participants with prodromal Alzheimer's disease or Mild Cognitive Impairment (MCI) were only included if conversion from MCI to Alzheimer's disease was confirmed in all participants by clinical follow–up. We made no restriction on participant's age, disease duration, or drug treatment. We only included studies with a longitudinal design, in which the putative biomarker and clinical measure were both measured at least twice, as this is the only appropriate design to use when developing a biomarker for disease progression. We included studies of any test used to investigate disease progression in Alzheimer's disease, including (but not restricted to) imaging, blood, CSF and neurophysiological tests. We looked for associations of the change in the test result over time with the change in any clinical measure of disease progression–impairment, global cognitive function, disability, handicap, and quality of life. Associations to individual symptoms, parts of scoring systems, mood, disease duration, complications related to therapy and treatment status were excluded. Only papers available in full and in English were included. We assessed study quality using criteria we developed after a recent similar systematic review in Parkinson's disease. Results: Fifty–nine studies were finally included. The most commonly examined biomarker was brain MRI, which was examined in 17 (29%) of the included studies. The median follow–up time in the included longitudinal studies was only 1.0 years (IQR 0.8–1.7). Included studies were generally of poor quality with small numbers of participants, applying excessive inclusion/exclusion criteria, with flawed methodologies and inappropriate statistical analyses. Conclusions: We found insufficient evidence to recommend the use of any biomarker for disease progression in Alzheimer's disease clinical trials at present. This finding may reflect the poor quality of most previous studies in this area. We, therefore, present a provisional roadmap for conducting future studies to develop biomarkers for disease progression in Alzheimer's disease.